Sexual Behavior and Knowledge among Adolescents with Perinatally Acquired Human Immunodeficiency Virus Infection Compared to HIV-Uninfected Adolescents at an Urban Tertiary Center in New Jersey - Kaushik, Ashlesha; Pineda, Carol; Kest, Helen (International Journal of Reproductive Medicine, 2016)
Background. Sexual behaviors and knowledge among PHIV-infected (PHIV+) adolescents in comparison with HIV-uninfected youths are not well understood and continue to be studied actively. Objective. To compare sexual behavior and sexual knowledge of PHIV+ and HIV-uninfected adolescents at an urban, tertiary-care center in New Jersey. Study Design. Modified Centers for Disease Control and Prevention (CDC) Youth Risk Behavior Surveillance questionnaire was administered to PHIV+ and HIV-uninfected adolescents to assess and compare sexual behavior and knowledge over a 1-year-period. Results. Twenty-seven PHIV+ and 100 HIV-uninfected adolescents were studied; 59% PHIV+ and 52% HIV-uninfected adolescents were sexually active. A significantly higher proportion of PHIV+ adolescents compared to HIV-uninfected adolescents reported ≥1 occasion of unprotected penetrative sex (p<0.0001) and reported multiple (>4) sexual partners (p=0.037). Significantly more PHIV+ males reported receptive anal intercourse (p<0.001). About 1/3 of adolescents in both groups were unaware that sexual abstinence can prevent HIV transmission and >80% adolescents in both groups did not consider multiple sexual partners a risk factor for HIV transmission. Only 25% PHIV+ adolescents reported disclosing their seropositive status to their first sexual partners. Conclusions. High risk sexual behaviors were significantly more prevalent among PHIV+ youths; however both groups demonstrated considerable gaps in sexual knowledge. There is an urgent need for heightening awareness about risky behaviors, interventions for prevention, and reproductive health promotion among adolescents.